TROTSKYIST OPPOSITION AS THE MANIFESTATION OF THE LEFT-RADICAL PROTEST IN 1926-1929, (BY THE EXAMPLE OF THE SOUTH OF RUSSIA) - Andrej Baranov (Гуманитарные и юридические исследования)
The relevance of the topic lies in specifying particular ideological and organizational forms of left radical protest in the face of the multi-layered society and authoritarian regime. The mechanisms of intra-elite delimitation in a one-party system are still to be clarified. The contradictions of the NEP were expressed in a concentrated form in the South of Russia, a large agrarian region. The article defines the regional features of the left radical ("Trotskyist") opposition in 1926-1929 on the materials of the South of Russia. The specific conditions of the Trotskyist opposition activity in the region during the initial period of the NEP are as follows: a greater role of agrarian policy issues and "Cossacks -nonresidents" class division, the consequences of a protracted Civil war that was especially severe in the region, a weighty layer of left-wing radicalism supporters in the party-state authorities. The Trotskist opposition in the region (1926-1927) consisted mainly of party and state employees, unemployed and veterans of war, as well as unskilled workers. It was almost completely a city phenomenon. Public opinion regarding the opposition shifted in 1926-1927 to the negative side for the government, which was explained by the growth of unemployment and inequality. The poor awareness of the workers about the opposition caused the effect of "inadequate hopes", the empowerment of Trotsky with idealized features. There was also an opposite impetus for the growth of support for the authorities due to the threat of war, the "left turn" of the VKP(b) to the winding-down of the NEP, which won in late 1927. The opposition sentiments of unskilled workers, a part of Red Army soldiers and Civil War veterans were caused by contradictions between the urban and rural communities, the rejection of bureaucracy and corruption. However, the protest against the decline in living standards, rising unemployment and social inequality was situational and did not challenge the Soviet system, heading into the channel of its "correction". Therefore, the slogans of creating an underground party, put forward by the Trotskyist opposition, did not find broad support.